Local Primary Hollow Modules and its Relation with Some Other Modules (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
To consider R is an abelian ring with an identical member and  is non-zero unitary left module over a ring R.  is said to be a Hollow Module (HM) if each proper sub-mod (sub-mod) of  is small. A local primary hollow module (LPHM) is defined as a generalization of HM. A module is said to be a LPHM if  has one primary sub-mod with each small sub-mods. Our paper studies the type of such modules and it introduces some essential concepts that elaborate this issue.